ANALISIS PENGELOLAAN BELANJA PEMERINTAH PADA ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN KUBU RAYA TAHUN 2008 2011 - WAHONO, JOKO (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This study aims to identify and analyze the management of government spending in the budget revenue and expenditure covering indirect expenditures and direct spending. The use of data in the analysis is Realized Budget Report (LRA) District stronghold Kingdom in 2008 to 2011. With good management of expenditure, local governments are expected to realize the fruits of development and creating services directed to the needs of the community area. This study uses a qualitative approach to the analysis of analytical tools used is the analysis of the ratio of expenditure, spending growth analysis, optimization analysis of expenditure, expenditure efficiency analysis and analysis of government budget allocations in support of the mission set forth in RPJMD Kubu Raya district. Results showed that the management of government spending Kubu Raya district average ratio of indirect expenditures greater than direct expenditures, indirect expenditures prefers budget contribution for the benefit expenditure. For the average capital expenditures in 2008-2011 amounted to 32.99% of the total expenditure, the annual spending growth occurs by prioritizing the provision and improvement of infrastructure in the public interest. In 2009 and in 2010 the management of government spending in Kubu Raya district is not good and is not optimal, in 2008 and 2011 as well as perform well and the optimal efficiency of spending. The allocation of budgets based on the achievement of performance targets RPJMD good to excellent strategic. Keywords: Shopping area, Managed Expenditure